LOW CARDIOVASCULAR RISK REDUCTION BEHAVIORS AMONG HYPERTENSIVES ATTENDING FOLLOW-UP CARE AT A TERTIARY-LEVEL HOSPITAL IN ADDIS ABABA, ETHIOPIA - Bekele, Daniel Mengistu; Gary, Rebecca A; Goshu, Dejuma Yadeta; Yalew, Alemayehu Worku; Higgins, Melinda K (International Journal For Research In Health Sciences And Nursing, 2022)
Introduction: Cardiovascular disease (CVD) outcomes in hypertensives are substantially influenced by risk-reduction behaviors. Even though hypertensives in Ethiopia have a high prevalence of behavioral risks for negative CVD outcomes, little is known about risk-reduction behaviors in this population. Therefore, this study aimed to investigate the CVD risk reduction behaviors among adult hypertensives in Addis Ababa, Ethiopia. Method: A cross-sectional design was used. A sample of 384 hypertensives was selected using a systematic random sampling technique from the hypertension clinic registry. Epi data version 3.10 was used to clean the data, and SPSS version 25.0 was used for analysis. Descriptive statistic was used to determine participants’ CVD risk reduction behavioral status. Bivariate chi-square test and ordinal logistic regression analyses were run to identify variables associated with participants' ranked CVD risk reduction behavioral status at the p-value < .05 cutoff for statistical significance. Results: The mean (± standard deviation) age of participants was 53.61 (± 12.34) years, (range, 30-82 years), and 51.2% were males. The majority (56.5%) of them were at low CV risk reduction practices. Only 45.1% were at target BP control. The absence of comorbidities (p < .001), clinic visits every 3 months for hypertension (p = .041), normal body mass index (p = .008), hypertension duration of 5–9 years (p = .034), and young age adults (p = .041) were the characteristics significantly associated with the high CVD risk reduction practice. Conclusion: Hypertensives' adoption of CVD risk reduction behaviors was low, with a variety of unmanaged risk factors and a few cardioprotective behaviors. Healthcare providers may improve patients’ CV risk-reduction behavior through teaching lifestyle changes and more frequent clinic visits.